Soft-tissue response to synthetic polymer implants made of cross-linked polyurethane and containing a biologically active substance, albucid or dacarbazine, in animals (Ukrainian Journal of Ophthalmology, 2026)
Background: It is an urgent task of the today’s science to search for and introduce biointegrable synthetic materials into medical practice.Purpose: To investigate the soft tissue response to the polymer sample implants made of cross-linked polyurethane with an immobilized biologically active substance, albucid or dacarbazine, in animals.Materials and Methods: Thirty Wistar rats were used to assess the soft tissue response to polymer sample implants under examination. The cross-linked polyurethane-based sample implants with an immobilized biologically active substance, albucid or dacarbazine, were used in the experimental study.Results: The development of the connective tissue capsule around the sample implant, with the capsule completely separating the implant from the surrounding host tissue, was observed at the early time points. Sample implant porosity contributed to cell migration and gradual ingrowth of tissue structures into the implants, which prevented fast implant resorption, and was indicative of the implant biocompatibility with the host tissues. The placement of albucid-containing polyurethane implants in experimental animals resulted in the surrounding host tissue responses typical of aseptic inflammation. The placement of the dacarbazine-containing polyurethane implant in the back of each animal resulted in apparent changes in surrounding host tissue typical for the inflammatory process. It is likely that dacarbazine from the dacarbazine-containing polyurethane sample implant was durably released in the host tissues surrounding the sample, and exerted some biologically active effect which resulted in persistent inflammation at the site of implantation.Conclusion: The albucid- and dacarbazine-containing polymer materials obtained seem promising, and might be widely used as soft tissue substitutes in restorative and reconstructive eye and maxillofacial surgery.
Keywords: implant placement; polyurethane; biological activity; soft tissue response; experiment